The employment of contract workers in organisations in Singapore - Koh, Wei Een (2015)
The study on the use of contract workers was conducted to understand the operation of the contract work system in Singapore. It analyzes the impact of the use of contract workers on human resource management (HRM) practices and also looks into the feasibility of using contract workers as a long-term solution to the tight labour market. Interviews were conducted with three organisations in the· manufacturing sector to gather the necessary information. Contract workers are used by organisations as an alternative form of employment. They provide flexibility which is needed to meet their fluctuating production demands. In the process, however, they also bring about problems such as high turnover rates. HRM practices such as compensation, training and disciplinary action are also affected as contract workers fall into a different category of workers from the organisation's employees. Labour shortage has been quoted as one reason for the existence of contract work system. Analysis indicates that in the short run, the contract work system can help to alleviate the problem. However, the shortage will still persist in the long run as the target labour pool supply remains unchanged. Contract workers lose out to the other workers in terms of benefits, employment security and career prospects. With no union protection, they could be targets for exploitation. Ambiguity in terms of responsibility for injuries sustained and subsequent compensation may also place the contract worker in a disadvantaged position. Although the organisation is held vicariously liable in view of its responsibility and control over the contract worker, the provision in the Workmen Compensation Act can sometimes override the organisation's responsibility. Besides, the organisation is required to pay any salary due to the contract worker to the contractor but the contractor may not pay it to the worker. The possibility of taking legal action to recover the sum, however, is ineffective as at times the contractor is nowhere to be found. All these negative aspects, coupled with the inability of the contract work system to curb the labour shortage problem suggest that the system may not be a viable long-term solution. The study thus recommends that companies should automate to reduce their demand for labour. It is believed that this is one of the best ways to counter the shrinking labour force. Flexible automation would be the best choice as it provides both economies of scale and scope. The employment of part-time employees is also a viable solution. Here the relationship of the worker to the employer is clearer and they can also provide the flexibility which companies require.